ОPTIMIZATION OF GROWING AND FEEDING OF DIFFERENT BREEDS OF RUMINANTS AND THEIR HYBRIDS WITH AN AVERAGE LEVEL OF FEEDING IN THE CONDITIONS OF THE CARPATHIAN REGION OF ВUKOVINA - Лесик, Оксана; Калинка, Андрій; Приліпко, Тетяна (SWorldJournal, 2022)
This article presents the results of research on the impact of average typical feeding and retention technologies for fattening bulls of different breeds, types and their mixtures of ruminants on live weight, average daily, absolute and relative gains. Th